Legal Pragmatism in Traditional Practices: Imam al-Shāfi'ī's Maslahah Analysis of Mbolo Weki in Bima Regency - Hasan, Hamzah; Daud, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to describe how the implementation of the Mbolo Weki Tradition of the Sakuru Village Community, Monta Subdistrict, Bima Regency, then to describe the Maslahah Value in the implementation of the Mbolo Weki Tradition of the Sakuru Village Community, Monta Subdistrict, Bima Regency. This type of research is descriptive qualitative. Data sources in this research are primary and secondary sources, data collection methods include observation, interviews, and documentation. The results of the analysis show that the Mbolo Weki tradition not only has cultural values, but also contains maslahah values that are in line with the principles of Islamic law according to al-Shafi'i madhhab. In al-Shafi'i's perspective, this tradition is considered to provide positive benefits for individuals and society. The values of solidarity, justice, and togetherness contained in Mbolo Weki are considered in accordance with the concept of maslahah in Islamic law. This research is expected to provide a deeper understanding of the relationship between local traditions and universal values in the context of Islamic law, especially the al-Shafi'i madhhab. The implications of this research are expected to support the maintenance and development of local traditions that are in accordance with Islamic values and can make a positive contribution to people's lives.